Klasifikasi Kebakaran Hutan Dan Lahan Dengan Algoritma You Only Learn One Representation - Rizki, Yoze; Yogi Alfinaldo; Soni; Sy, Yandiko Saputra; Rahmad Firdaus (Computer Science and Information Technology, 2023)
Forest areas have a function of storing carbon dioxide and producing oxygen from trees and plants. The function of forests is very important for life, so forests are highly protected. One solution that can be taken is to take preventive measures, namely monitoring fire hotspots in forest and land areas by air. This research was tested using the same dataset as the YOLO (You Only Look Once) algorithm against the You Only Learn One Representation (YOLOR) algorithm with a train data division model of 1188 image data and test data of 75 image data with mAP results of 66.36%. . So it can be confirmed that the YOLOR algorithm is better than the YOLO algorithm which gets an mAP value of 50.65%.